Continuous improvement in a cheese bread factory in São Paulo: A case study (Research, Society and Development, 2021)
The market is becoming progressively more competitive, which makes the continuity of an organization more difficult, because to ensure its market share it must remain competitive, with continuous improvement in the manufacturing process and results. This study developed a study of the production process of a small cheese bread production company in the city of São Paulo. A case study was carried out, initiated with research on the company's production process, with the assumption of a bibliographic survey on the Kaizen process and philosophy, in conjunction with the 3Ms and GUT Matrix tools. Quantitative and qualitative data were considered, which allowed the analysis of the company's points of vulnerability and the need for improvement. Points of improvement were detected in the production process, specifically in the physical rearrangement, with the unnecessary movement of materials and people, as well as maintenance in the furnaces. From the tools used, it was possible to map the production process, find the biggest problems and work in partnership with the employees and the owner to implement optimized solutions for the company with reduced handling and increased production.